Effects of omega-3 polyunsaturated fatty acids on cellular development in human ovarian granulosa tumor cells (KGN) - Yao, Yilin; Tian, Shen; Li, Ningxin; Yang, Yanzhou; Zhang, Cheng (Frontiers in Nutrition, 2022)
Emerging research has shown that polyunsaturated fatty acids (PUFAs) benefit human health and exert anti-cancer effects. However, there is little understanding of the specific mechanisms by which PUFAs regulate the cells of the ovarian granulosa tumor. In the current study, we investigate the effects and the possible mechanisms of PUFAs on human ovarian tumor cells development. KGN cells were treated with omega-3. Small interfering (siRNA) and specific activator were used to knock down and overexpress gene expression in KGN cells. The protein content levels were analyzed by Western blot. Cell viability, proliferation and apoptosis assay were performed to examine the cellular development. And the level of glucose uptake in KGN cells were assessed by 2-DG measurement. The results showed that omega-3 treatment reduced cell viability, proliferation and increased cell apoptosis. Further studies showed that omega-3 also reduced GLUT1/4 protein content and cellular glucose uptake. Subsequent knockdown and overexpression of OCT4 using Oct4 siRNA and O4I2 (OCT4 activator) showed that OCT4 was involved in the regulations of omega-3 on GLUT1/4 expression and cell development. Our data demonstrate that omega-3 inhibits cellular development by down-regulating GLUT1/4 expression and glucose uptake in KGN cells, which are mediated through OCT4.